Dielectric characterization of sugar mill wastewater and its impact on soil properties in the khadar and bangar regions - Ankur Kumar; Prachi Palta; Aastha Palta; Sanjay Dhanka; Rohit Bansal; Mochammad Fahlevi; Fazla Rabby; Mohammed Aljuaid (Scientific Reports)
Abstract This study investigates the dielectric properties of sugar mill wastewater and its impact on surrounding soils and crops, prompted by the environmental pollution resulting from the rapid expansion of sugar mills. By examining the dielectric characteristics of this wastewater and its effects on soil properties, the research emphasizes the urgent need for effective management strategies to mitigate the environmental impact of sugar mill operations. Soil samples were gathered from Uttar Pradesh, India, using a multistage sampling approach. A Dak-12 open-ended coaxial probe paired with a two-port Vector Network Analyzer (model E5071C from Agilent Technologies) was used to assess the dielectric characteristics of these soils. Samples from the Khaddar and Bangar regions were examined to determine how the dielectric properties (both real part ε’ and imaginary part ε’’) were influenced by contaminants from sugar mills. Predictive models, including artificial neural networks (ANNs) and regression trees, were applied to forecast the dielectric responses. The physicochemical analysis of wastewater revealed significant contamination, with a color range from light brown to black, pH values between 7.63 and 6.26, suspended solids of 40 to 45%, and conductivity of 1222 ± 12.06 to 1313 ± 10.62 µS/cm. Dielectric measurements indicated that the average ε’ decreased from 109.04 to 72.61 at 10 MHz and from 38.48 to 25.69 at 3 GHz as temperature rose from 0 to 60°C. In Khaddar soil, ε’ decreased from 37.45 to 15.62, while ε’’ increased from 149.24 to 232.52. Bangar soil exhibited ε’ values decreasing from 60.1 to 49.74 and ε’’ rising from 110.55 to 523.88. Machine learning models achieved R² values of 0.9961 for ε’ and 0.9594 for ε’’. This research highlights the critical role of dielectric properties in assessing sugar mill wastewater quality and its adverse effects on soil and crop health, advocating for sustainable practices to mitigate these impacts.